Implementasi Metode Simple Additive Weighting Pada Perancangan Sistem Penilaian Reseller di Showroom Aska Motor Garage - Yulianingsih, Yulianingsih; Megiati, Yunita Endra; Ananda, Rizki (Faktor Exacta, 2024)
Aska Motor Garage Showroom is a company engaged in motorcycle sales. As a sales-oriented business, Aska Motor Garage needs a strategy to boost its sales. One of the strategies that can be implemented is by establishing partnerships with resellers through the provision of rewards in the form of incentives. Therefore, there is a need for an objective and measurable assessment system. The Simple Additive Weighting method is one of the techniques used to determine the best value based on criteria and weights that can be customized according to the partners' needs, and it is considered quite appropriate for use in this research. The result of this system design is a decision support system that provides information about the assessment of the top resellers, using four supporting criteria, including monthly sales, innovation, work quality, and adherence to target pricing.